PERSEPSI SISWA SMA KOTA BANDA ACEH TENTANG KONTRIBUSI PAI DALAM PENANAMAN PEMAHAMAN SYARI’AT ISLAM DI ACEH - Huwaida (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2023)
This study aims to determine students' perceptions regarding the contribution of Islamic Religious Education (PAI) subjects in cultivating an understanding of Islamic law in Aceh. A qualitative approach using the case study method is used. Data obtained through interviews with five participants. Data were analyzed using thematic analysis techniques. The results of this study indicate that there is contribution of Islamic Religious Education (PAI) subjects in the form of students having knowledge of Islamic law applied in Aceh and students having knowledge of the categories of violations of Islamic law. Categories of violations of Islamic law that students know are drinking alcoholic beverages; maisir (gambling); khalwat (obscene) and wearing clothes that are not in accordance with the Shari'a law. The categories of punishment known to students for violations committed were caning for adultery.